Does Collaborative Inquiry Project Laboratory Promote Teenagers' Problem Solving Skills?: A Feasibilty study - ., Nurhafidhah; ., Nursamsu; Fitria, Liza (Journal of Ecohumanism, 2024)
This research aims to test the effectiveness of Collaborative Inquiry Project Laboratories in enhancing problem-solving skills among adolescents. Problem-solving skills are one of the essential competencies needed to face challenges in the modern era, particularly in the context of 21st-century education. The research method used is a quasi-experimental design with a pretest-posttest control group. The research sample consists of high school students divided into experimental and control groups. The experimental group engaged in collaborative inquiry project-based learning, while the control group followed conventional learning methods. The results indicate a significant improvement in the problem-solving skills of adolescents involved in the collaborative inquiry project laboratory compared to the control group. This suggests that the inquiry project-based learning approach, which emphasizes collaboration, can be an effective strategy for developing adolescents' problem-solving abilities. These findings are expected to contribute to the development of learning models that support 21st-century skills, particularly in science education.